Elicitation with Sodium Silicate and Iron Chelate Affects the Contents of Phenolic Compounds and Minerals in Buckwheat Sprouts - Henryk Dębski; Wiesław Wiczkowski; Dorota Szawara-Nowak; Marcin Horbowicz (Polish Journal of Food and Nutrition Sciences)
The study concerned the effect of elicitors on the contents of free flavonoids and phenolic acids, as well as their esters and glycosides, and contents of minerals in 7-day sprouts of common buckwheat. An aqueous solution containing a mixture of sodium silicate and Fe-EDTA (SIL-Fe) was compared with the same concentration of sodium silicate alone (SIL) and water (control). Phenolic compounds were analysed using an HPLC–MS/MS apparatus equipped with an ion-trap mass spectrometer, and analyses were conducted by multiple reaction monitoring of selected negative ions. The contents of macro- and microelements in sprouts were determined by the ICP-AES method, after sample mineralization in a mixture of HNO 3 and H 2 O 2 . The study showed that SIL-Fe influenced the accumulation of individual phenolics in buckwheat sprouts in different ways. Among the major flavonoids in the buckwheat sprouts treated with SIL-Fe, the content of free forms and esters of (‒)-epicatechin and glycosides of quercetin as well as the total content of flavonoids decreased. Elicitation of buckwheat sprouts with SIL and SIL-Fe reduced the contents of calcium, potassium, copper, and zinc; however, the SIL-Fe treatment caused a 5-fold increase in iron content and a 2-fold increase in silicon content. The ratio of total flavonoids to the iron content of SIL-Fe-treated sprouts was 11.5, which was substantially lower than in the control, where it reached 64. The results of this study indicate that it is possible to produce buckwheat sprouts with a high content of flavonoids and fortified with iron, which may increase the availability of this element.